2016
DOI: 10.18632/oncotarget.12066
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating clinical and prognostic implications of Glypican-3 in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most deadly cancers worldwide. In patients with HCC, histopathogical differentiation is an important indicator of prognosis; however, because determination of HCC differentiation is difficult, the recently described immunohistochemical (IHC) marker glypican3 (GPC3) might assist in HCC prognostication.The goal of our study was to investigate GPC3's IHC staining pattern and define the relationship between its expression and patients' clinicopathologic features and ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 61 publications
3
31
0
Order By: Relevance
“…This finding is consistent with previous reports (26,27). It has been reported that GPC3 is expressed in cancerous cells as well as non-cancerous surrounding cells, and that the prognosis of GPC3-positive HCC patients is poor (12,14,28,29). This may indicate that FL-GPC3 is produced by the tumor itself but as well as by precancerous lesions located in the surrounding liver tissue.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with previous reports (26,27). It has been reported that GPC3 is expressed in cancerous cells as well as non-cancerous surrounding cells, and that the prognosis of GPC3-positive HCC patients is poor (12,14,28,29). This may indicate that FL-GPC3 is produced by the tumor itself but as well as by precancerous lesions located in the surrounding liver tissue.…”
Section: Discussionsupporting
confidence: 93%
“…Many studies have reported that GPC3 expression is correlated with a poor prognosis in HCC [ 38 , 39 ], and that GPC3 may be a prognostic marker for curative resection [ 40 , 41 , 42 ] and HCC recurrence following liver transplantation [ 43 ]. Two meta-analyses recently indicated that GPC3 overexpression was significantly associated with poor prognosis in patients with HCC [ 44 , 45 ].…”
Section: Cell Surface Proteoglycan (Glycosylphosphatidylinositol-amentioning
confidence: 99%
“…Glypican-3 (GPC-3), a special marker of HCC, has been used to identify the HCC from other tumors and to evaluate the prognosis. GPC-3 is a member of the glypican family, which influences cell growth, differentiation, and migration [15]. GPC-3 is highly expressed in HCC, but not in cholangiocarcinoma or normal hepatic cells and is low express in well differential HCC [16,17].…”
Section: Backgroudmentioning
confidence: 99%
“…GPC-3 is highly expressed in HCC, but not in cholangiocarcinoma or normal hepatic cells and is low express in well differential HCC [16,17]. Previous studies have shown that higher GPC-3 expression level in HCC is a risk factor for shorter overall survival (OS) and levels of GPC-3 expression in poorly-differentiated tumor cells were higher than moderately-and well-differentiated HCC [15,18].…”
Section: Backgroudmentioning
confidence: 99%